Youth Empowerment Programs and Socio-Economic Development in Gombe State: An Assessment of N-Teach 2016-2021 - Doho, Ahmed Wali; Galadima , Mohammed Musa; Yusuf, Mohammed (Kashere Journal of Politics and International Relations, 2024)
This study seeks to examine the role of the N-Teach Program on youth empowerment in Gombe state. The study used both the primary and secondary sources of data. At the end of the research, it was revealed that there is a strong relationship between N-Teach Program and youth and empowerment in the state. To improve on the achievements so far made, the study recommended that Government should put in place certain mechanisms that can regulate the activities of the bureaucrats and involve stakeholders in the implementation and monitoring of such the program.